Resistance of Regional Governments in the Implementation of E-Government (Universitas Terbuka, 2024)
According to the UN E-Government Survey, Indonesia achieved a High E-Government Development Index (EDGI) rating with a score of 0.6612 and ranked 88th out of 193 countries. However, monitoring and evaluation results conducted by the Ministry of Administrative and Bureaucratic Reform presented a different outcome. The implementation of e-government at the regional government level shows that 20.63% still received a poor rating, and 50% received a fair rating. Meanwhile, in central institutions, only 7% received a poor rating, while 54% received a good rating and 13% received a very good rating. Based on this data, the implementation of e-government is not consistent or well distributed, and it is suspected that there is resistance to the implementation of e-government in some regional governments. This article uses a literature study approach by reviewing various relevant sources, including journals, books, scientific reports, and other documents. The results of this study indicate that the resistance at the regional government level is caused by several factors, namely mindset, human resource capacity, regulations, infrastructure, and finance.